Policy Implementation and Regulatory Challenges in Managing Civil Service Resources in the Era of Digital Governance - Salmah Harun (Golden Ratio of Social Science and Education, 2026)
This study investigates the dynamics of policy implementation and regulatory challenges in managing civil service resources within the evolving framework of digital governance. The research aims to interpret how digital transformation reshapes administrative structures, human resource management, and regulatory coherence in the public sector. Employing a qualitative descriptive approach based on a systematic literature review, the study synthesizes empirical and conceptual evidence from recent academic and institutional publications between 2013 and 2025. Data were analyzed thematically through interpretive synthesis to identify recurring patterns of policy adaptation, institutional capacity, and regulatory reform across different governance contexts. The findings reveal that digital governance transforms policy implementation from a linear bureaucratic process into an adaptive, data-driven, and network-based system that demands interagency coordination and technological proficiency. Regulatory challenges emerge from outdated legal frameworks, fragmented institutional mandates, and limited digital literacy among civil servants, leading to uneven implementation outcomes. The study highlights that effective civil service resource management requires integrating digital competency frameworks, ethical data governance, and agile leadership within coherent regulatory systems. Theoretically, this research contributes to modernizing implementation theory by embedding digital institutionalism and adaptive capacity concepts, while managerially, it offers a model for aligning human resource policies with sustainable digital transformation. The results affirm that sustainable digital governance depends on the continuous interaction between policy innovation, regulatory adaptability, and institutional learning.